Avaliação de potencialidades e aplicações de espectrômetros com plasma acoplado indutivamente em análises químicas - Vieira, Edivan Carvalho (Universidade Federal de São Carlos, 2007)
This work is divided in two main parts. In the first one, the operating conditions of a radially inductively coupled plasma optical emission spectrometry (ICP OES) was evaluated in soil and vegetable materials analysis. A factorial design was performed to systematic evaluation of the equipment operating conditions, being established: 1.05 kW power, 0.6 L min-1 flow gas nebulization and 8 mm observation height as operating conditions to Ca, Fe, K, Mg, Mn, Na, P, and Zn determination in the studied samples, certified materials (NIST, Peach Leaves and Corn Bran), digested in different oxidant media. The recoveries of Cu, Fe, Mn, and Zn in soil extracts (IAC 274 and NIST San Joaquim Soil) were also evaluated in the same established conditions. A protocol was established for use of the equipment in routine analysis. In the second part of this work, the bioavailability of iron-proteins in different crude and processed foods was evaluated. Two different media were used to metalloprotein extraction: Tris buffer 5,0x10-3 mol L-1 and simulated gastric fluid. An inductively coupled plasma mass spectrometer (ICP-MS) was used to determine Fe in the extract solutions and a size exclusion column (SEC) coupled to UV-ICP-MS detectors was used to metalloprotein speciation. The results indicated that the cooking caused significant changes in the amounts of Fe bond to proteins from beefs and seaweeds, although the elements were still bioavailables.
Evaluation of potencialities and aplications of inductively coupled plasma spectrometers in chemical analysis
Keywords: Espectrometria de massa - métodos; Biodisponibilidade; ICP-OES; ICP-MS; Solos; Plantas; CIENCIAS EXATAS E DA TERRA::QUIMICA